Childhood exposure to hunger: associations with health outcomes in later life and epigenetic markers - Perna, Laura; Zhang, Yan; Wild, Beate; Kliegel, Matthias; Ihle, Andreas; Schöttker, Ben; Mons, Ute; Brenner, Hermann (Epigenomics, 2020)
Aim: To assess associations of early exposure to hunger with depressive symptoms and cardiovascular disease (CVD) and to investigate possible epigenetic pathways. Patients & methods: Data were based on a German population-based cohort of older adults (n = 9631). Regression models were performed for health outcomes in later life. An epigenome-wide association study for early-life exposure to hunger was performed in a subgroup (n = 2221) with whole blood DNA methylation data. Results: Childhood exposure to hunger was associated with CVD and depressive symptoms in later life. Prenatal or infant exposure was strongly associated with depressive symptoms. No CpG reached epigenome-wide significance after multiple testing correction. Conclusion: Childhood hunger is a risk factor for depressive symptoms and CVD at older age. DNA methylation could not explain this association.
Gesehen am 22.03.2024